SIRT6 Suppresses NFATc4 Expression and Activation in Cardiomyocyte Hypertrophy - Li, Zhenzhen; Zhang, Xiaoying; Guo, Zhen; Zhong, Yao; Wang, Panxia; Li, Jingyan; Li, Zhuoming; Liu, Peiqing (Frontiers in Pharmacology, 2019)
NFATc4, a member from the Nuclear Factor of Activated T cells (NFATs) transcription factor family, plays a pivotal role in the development of cardiac hypertrophy. NFATc4 is dephosphorylated by calcineurin and translocated from the cytoplasm to the nucleus to regulate the expression of hypertrophic genes, like brain natriuretic polypeptide (BNP). The present study identified SIRT6, an important subtype of NAD+ dependent class Ⅲ histone deacetylase, to be a negative regulator of NFATc4 in cardiomyocyte hypertrophy. In phenylephrine (PE)-induced hypertrophic cardiomyocyte model, overexpression of SIRT6 by adenovirus infection or by plasmid transfection repressed the protein and mRNA expressions of NFATc4, elevated its phosphorylation level, prevented its nuclear accumulation, subsequently suppressed its transcriptional activity and downregulated its target gene BNP. By contrast, mutant of SIRT6 without deacetylase activity (H133Y) did not demonstrate these effects, suggesting that the inhibitory effect of SIRT6 on NFATc4 was dependent on its deacetylase activity. Moreover, the effect of SIRT6 overexpression on repressing BNP expression was reversed by NFATc4 replenishment, whereas the effect of SIRT6 deficiency on upregulating BNP was recovered by NFATc4 silencing. Mechanistically, interactions between SIRT6 and NFATc4 might possibly facilitate the deacetylation of NFATc4 by SIRT6, thereby preventing the activation of NFATc4. In conclusion, the present study reveals that SIRT6 suppresses the expression and activation of NFATc4. These findings provide more evidences of the anti-hypertrophic effect of SIRT6, and suggest SIRT6 as a potential therapeutic target for cardiac hypertrophy.